Caribbean telecommunications policy : the regional integration link. - Noguera, Felipe (1991)
Highlights the need for regulatory bodies and mechanisms to identify, safeguard and promote the interest of the peoples of the Caribbean with respect to telecommunications. Describes the possible role which the Caribbean Association of National Telecommunications Organizations (CANTO) can play in the formulation of regional and national telecommunication policies.